Curbing corruption : practical strategies for sustainable change - Spector, Bertram I. (Bertram Irwin), 1949- (New York : Routledge, 2022)
"Many anti-corruption efforts have had only a minimal effect on curbing the problem of corruption. This book explains why that is, and shows readers what does work in the real world in the fight against corruption, and why. Counter-corruption initiatives often focus on the legal, institutional and contextual factors that facilitate corrupt behavior, but these have had only nominal impacts, because most of these reforms can be circumvented by government officials, powerful citizens and businesspeople who are relentless in their quest for self-interest. This book argues that instead, we should target the key individual and group drivers of corrupt behavior and through them promote sustainable behavioral change. Drawing on over 25 years of practical experience planning, designing and implementing anti-corruption programs in over 40 countries, as well as a wealth of insights from social psychological, ethical and negotiation research, this book identifies innovative tools that target these core human motivators of corruption, with descriptions of pilot tests that show how they can work in practice. Anti-corruption is again becoming a priority issue, prompted by the emergence of more authoritarian regimes, and the public scrutiny of government responses to the COVID-19 pandemic. Straddling theory and practice, this book is the perfect guide to what works and what doesn't, and will be valuable for policy-makers, NGOs, development practitioners, and corruption studies students and researchers"--
Since the Dawn of HumankindPART 1. LESSONS LEARNEDAre We on the Right Track?Legal and Institutional Reform Programming: What Works?Preventing Corruption through Accountability, Transparency and Governance Programming: What Works?Civil Society Engagement: What Works?Anti-Corruption Programming in Post-Conflict SocietiesPART 2. NEW STRATEGIESActivating Behavioral Change Initiatives The View through an Ethical LensThe Social Psychological LensDeconstructing Negotiations to Make Bribery FailPART 3. PRACTICAL IMPLEMENTATIONWhatś Next? Assessments, Strategies and ImplementationCase Study: Ukraine Assessment (2005)Additional Implementation Issues to ConsiderSustaining Anti-Corruption ReformsMaking Corruption FailAppendix: Corruption Assessment
OCLC-licensed vendor bibliographic record.
Keywords: Corruption -- Prevention; SOCIAL SCIENCE / Third World Development